The Soul of Christianity Restoring the Great Tradition - Smith, Huston (San Francisco Harper & Brothers Publishers, 2005)
The author outlines the essential teachings of Christianity as well as his own beliefs, citing the differences between liberal and fundamentalist practices while arguing for a return to a more traditional Christian belief system.
Keywords: Christianity. Christianisme